The effect of cocaine on gastric mucosal PGE2, LTC4 and ulcerations - L. D. G. Angus; T. A. Stein; L. J. Auguste; J. Gintautas; J. Westervelt; L. Wise; G. W. Shaftan (Hindawi Limited, 1993)
The association between cocaine use and acute gastroduodenal perforation is known. The effect of cocaine and stress on gastric mucosal ulceration and the levels of prostaglandin E2 (PGE2) and leukotriene C4 (LTC4) was studied in 40 Sprague-Dawley rats. Controls received intraperitoneal (i.p.) saline, ten received i.p. cocaine (35 mg/kg), ten were stressed by the cold restraint method, and ten had i.p. cocaine and stress. Cocaine alone did not induce ulceration, but decreased PGE2 levels. Stress alone caused ulceration, but was not associated with a change in either PGE2 or LTC4 levels. When combined with stress, however, cocaine caused a three-fold increase in ulceration and a significant increase in PGE2 and LTC4 levels. Stress may predispose the cocaine addict to loss of gastroduodenal mucosal integrity, which is related to an imbalance of PGE2 and LTC4 synthesis.